Ce ion doped high-density gadolinium borosilicate scintillation glass and preparation method thereof

By adding GdF3 and Gd2O3 to the scintillation glass and sensitizing Ce3+ luminescence, the existing scintillation glass density and cost problems are solved, and the high density and high light yield is achieved, which is suitable for applications in the field of ray detection.

CN119569336APending Publication Date: 2025-03-07BEIJING GLASS RES INST +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311134989.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-05
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Existing scintillation glasses have challenges in terms of density and cost, making it difficult to achieve both high density and low cost, especially when they contain heavy metal oxides, which have problems of environmental pollution and low light yield.

Method used

By adding a large amount of GdF3 and Gd2O3 to the borosilicate glass as the glass matrix, the density of the scintillation glass is increased, and Ce3+ luminescence is sensitized to increase the light yield.

Benefits of technology

The preparation of high-density scintillation glass is achieved, with a density of 6g/cm3, which increases the light yield and reduces the preparation cost, making it suitable for large-scale production and promotion applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses Ce < 3 + > doped high-density gadolinium borosilicate scintillation glass and a preparation method thereof. The Ce < 3 + > doped high-density gadolinium borosilicate scintillation glass comprises the following components: SiO2, B2O3, Al2O3, BaF2, GdF3, Gd2O3 and CeF3. The invention relates to a preparation method of high-density gadolinium borosilicate scintillation glass, a scintillation glass matrix comprises SiO2, B2O3, Al2O3, BaF2, GdF3, Gd2O3 and a luminescent center Ce < 3 + > dispersed in the matrix, the proportion of each component in the matrix is as follows: SiO2: 17-31 mol%, B2O3: 17-25 mol%, Al2O3: 3-10 mol%, BaF2: 0-10 mol%, GdF3: 0-30 mol%, Gd2O3: 15-34 mol%, the content of the luminescent center Ce < 3 + > is 0-2 mol%, and the sum of the proportions of the components is 100%. According to the preparation method of the Ce < 3 + >-doped high-density gadolinium borosilicate scintillation glass, a large amount of GdF3 and Gd2O3 are added through a high-temperature melting method, the high-density and high-light-yield Ce < 3 + >-doped high-Gd < 3 + >-concentration borosilicate scintillation glass is prepared in the N2-H2 atmosphere, and the Ce < 3 + >-doped high-Gd < 3 + >-concentration borosilicate scintillation glass has wide potential application value in the aspects of industrial detection, nuclear physics and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a high-density gadolinium borosilicate scintillating glass, and in particular to a Ce 3+ The invention discloses high-gadolinium-doped borosilicate glass scintillation glass and a preparation method thereof, belonging to the field of luminescent materials. Background Art

[0002] Scintillating materials are optically functional materials that can convert X-rays, gamma rays and other high-energy particles into ultraviolet and visible light. They play an extremely important role in high-energy physics experiments, nuclear medicine imaging, anti-terrorism security inspections, oil exploration and other fields, especially in the construction of high-energy physics calorimeters and nuclear medicine imaging equipment. They are widely used and in great demand. Scintillating crystals are currently the most studied and widely used scintillators, such as Bi4Ge3O: (BGO), PbWO4: (PWO), etc. However, the growth cycle of scintillating crystals is long, the process is complex, and the crystal size and shape are limited, which results in high cost of scintillating crystals. In particular, traditional crystal growth technology is difficult to ensure high concentration and uniform distribution of doped ions, and thus it is difficult to optimize the optical properties of the material, which greatly limits its promotion and application. Scintillating glass has excellent optical properties and stable chemical properties. In particular, glass is low in cost and has experience in large-scale production. It is expected to replace some single crystals used in high-energy physics and other fields, and has broad application prospects.

[0003] High density is an important indicator of inorganic scintillating materials. High-density scintillators have stronger stopping power for high-energy particles and shorter irradiation length, which can improve the spatial resolution of detectors and is very beneficial to the miniaturization design of instruments or projects. In practical applications, the density of scintillating glass should preferably reach 6g / cm 3 However, the density of the scintillating glass reported so far is difficult to achieve this standard, and most of the glass components with higher density contain heavy metal oxides such as PbO, Bi2O3, and Lu2O3. For example, Chinese patent publication CN 1087066A discloses a high-density scintillating glass with PbO and Bi2O3 as the main components, the remainder being glass-forming oxide components, and the luminescence center being PbO and Bi2O3. The scintillating glass contains a large amount of PbO, which seriously pollutes the environment. In addition, although Pb and Bi can effectively increase the density of the glass, they will reduce the light yield of the scintillating glass, and the radiation luminescence efficiency of this type of scintillating glass is very low, which also limits its further practical application. For example, patent publication number CN 107759079 B increases the glass density to 6g / cm by adding heavy rare earth Lu2O3 to the glass. 3 , which enhances the radiation resistance of the glass, but it contains a large amount of expensive Lu2O3, which makes the cost high and is not conducive to reducing the cost performance of the scintillating glass, thus limiting the promotion and application of this type of scintillating glass.

[0004] In order to solve the above problems existing in the prior art, the present invention improves the density of the scintillating glass by co-doping GdF3 and Gd2O3 as the glass matrix, has a higher light yield and good physical and chemical properties, and is a scintillating glass with extremely wide applications. Summary of the invention

[0005] In order to solve the above problems existing in the background technology, the object of the present invention is to provide a Ce 3+ High-density gadolinium-doped borosilicate scintillating glass and its preparation method. The scintillating glass has good optical and mechanical properties and good chemical durability, and has the advantages of high solubility in rare earth oxides. The present invention selects to add a large amount of GdF3 and Gd2O3 to the borosilicate glass component as a glass matrix to increase the density of the scintillating glass and sensitize Ce. 3+ Luminescence effectively improves the light yield of the scintillating glass, greatly reduces the preparation cost of high-density scintillating glass, and is easy to achieve large-scale production. It can better realize the promotion and application of X-ray detection fields such as real-time X-ray imaging, industrial online detection, scientific research, and national security monitoring.

[0006] The present invention provides a Ce 3+ A method for preparing doped high-density borosilicate scintillating glass, the scintillating glass comprising a matrix of SiO2, B2O3, Al2O3, BaF2, GdF3, Gd2O3 and a luminescent center Ce dispersed in the matrix 3+ The proportions of the components in the matrix are: SiO2: 17-31mol%, B2O3: 17-25mol%, Al2O3: 3-10mol%, BaF2: 0-10mol%, GdF3: 0-30mol%, Gd2O3: 15-34mol%, and the luminescent center Ce 3+ The content is 0-2mol%, and the sum of the proportions of the above components is 100%.

[0007] The present invention uses SiO2 and B2O3 as the main components of glass. The addition of B2O3 is conducive to reducing the melting temperature of glass; the addition of Al2O3 is conducive to inhibiting the occurrence of glass phase separation; BaF2 can reduce the phonon energy of glass, reduce the probability of non-radiative relaxation, and reduce the radiation length of glass; among them, GdF3 and Gd2O3 have larger atomic masses, and Gd 3+ The radius is moderate and can effectively form ionic solid solutions with most glass matrices. 3+ Can transfer energy to the luminescent center Ce 3+Therefore, the present invention uses high content of co-doped GdF3 and Gd2O3 to significantly improve the glass density and luminous efficiency of the obtained sample, which can better meet the requirements of high-energy ray and high-energy particle detection, high-energy physics experiments and nuclear science experiments.

[0008] The present invention provides a Ce 3+ A method for preparing high-density gadolinium-doped borosilicate scintillating glass comprises: Using Si source, B source, Al source, Ba source, Gd source and Ce source as raw materials, mixing them evenly according to the molar components of the scintillating glass to obtain raw material powder; The raw material powder is melted at 1400-1450°C for 60-80 minutes to obtain a glass melt; the glass melt is poured into a metal mold preheated to 550-600°C, annealed for 2-4 hours after casting, and then cooled to room temperature in the furnace to obtain the scintillation glass.

[0009] Preferably, the Si source is stone powder.

[0010] Preferably, the B source is B2O3, which is introduced in the form of H3BO3.

[0011] Preferably, the Al source is Al2O3, which is introduced in the form of Al(OH)3.

[0012] Preferably, the Gd source is GdF3, Gd2O 3。

[0013] Preferably, the Ba source is BaF2.

[0014] Preferably, the Ce source is CeF3.

[0015] Preferably, the purity of the above raw materials is at least analytically pure.

[0016] Preferably, the annealing treatment is performed at a temperature of 550-600° C. for 2-4 hours.

[0017] The present invention has the following advantages: 1. The present invention 3+ The preparation process of gadolinium-doped borosilicate scintillating glass is simple, the preparation cycle is short, the chemical composition is easy to adjust, large size can be easily achieved, it can be fiberized, and it has good chemical stability; 2. The present invention 3+ The gadolinium-doped borosilicate scintillating glass does not contain PbO, is friendly to the human body and the environment, and does not contain precious metal oxides such as Lu2O3 and GeO2, which is conducive to reducing the preparation cost of high-density scintillating glass and is easy to achieve large-scale production, promotion and application; 3. Ce of the present invention3+ The gadolinium-doped borosilicate scintillation glass is rich in GdF3 and Gd2O3. In particular, GdF3 as a heavy metal fluoride not only has high density, but also can be used as a flux to reduce the glass melting temperature and increase the solubility of rare earth oxides in the glass. The total content of GdF3 and Gd2O3 in the scintillation glass component obtained by the present invention is up to 59 mol%, and the mass fraction reaches 80.27%, which can significantly increase the density of the glass to 6 g / cm 3 , Gd 3+ Can transfer energy to Ce 3+ Luminescent center, thereby improving luminous efficiency, 137 The maximum light yield under Csγ-ray excitation can reach 1116ph / Mev. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The actual photographs of the scintillating glass obtained in Examples 1-5 of the present invention; Figure 2 is the transmission spectrum of the scintillating glass obtained in Examples 1-5 of the present invention; Figure 3 The decay time measurement spectrum of the scintillation glass obtained in Examples 1-4 of the present invention; Figure 4 are actual photographs of the scintillating glass obtained in Examples 6-10 of the present invention; Figure 5 is the transmission spectrum of the scintillating glass obtained in Examples 6-10 of the present invention; Figure 6 This is a measurement graph of the decay time of the scintillation glass obtained in Examples 6-10 of the present invention. DETAILED DESCRIPTION

[0020] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0021] The present invention uses SiO2 and B2O3 as main components and adds a large amount of GdF3 and Gd2O3 to prepare a Ce 3+ High-density gadolinium-doped borosilicate scintillating glass. The scintillating glass is prepared by a high-temperature melting process in a N2-H2 atmosphere. The scintillating glass includes a matrix and a luminescent center. The proportions of the components in the matrix are: SiO2: 17-31mol%, B2O3: 17-25mol%, Al2O3: 3-10mol%, BaF2: 0-10mol%, GdF3: 0-30mol%, Gd2O3: 15-34mol%, and the luminescent center Ce 3+The content is 0-2mol%, and the sum of the proportions of the above components is 100%.

[0022] The following is an exemplary description of the Ce provided by the present invention. 3+ Preparation method of high-density gadolinium-doped borosilicate scintillating glass.

[0023] According to the composition formula of scintillation glass, SiO2 raw material, B2O3 raw material, Al2O3 raw material, BaF2 raw material, GdF3 raw material, Gd2O3 raw material and CeF3 raw material are weighed and mixed evenly to obtain mixed powder. The SiO2 raw material is stone powder, the B2O3 raw material is H3BO3, the Al2O3 raw material is Al(OH)3, and other scintillation glass components are introduced with the raw materials, and the purity of the above raw materials is at least analytical grade.

[0024] Pour the ground raw materials into a corundum crucible, put it into a high-temperature electric furnace at 1400-1450°C and keep it warm for 70-80 minutes to obtain a uniform glass melt. The melting atmosphere is a N2-H2 mixed gas.

[0025] The melt is poured into a mold preheated to 550-600°C, and the formed glass is quickly placed in a muffle furnace at 550-600°C for 2-4 hours for annealing.

[0026] The obtained glass is annealed to eliminate internal stress. The annealing temperature can be 550-600°C and the annealing time is 2-4 hours. Then the temperature is cooled to room temperature along with the furnace to obtain a primary scintillating glass.

[0027] The scintillating glass primary product is processed into the scintillating glass of the present invention after cutting, surface grinding and polishing.

[0028] Ce in the present invention 3+ Doping high-density gadolinium borosilicate scintillating glass, by increasing the content of GdF3 and Gd2O3, sensitizes Ce 3+ The invention uses the traditional high-temperature melting method, which is easy to realize large-scale production, promotion and application.

[0029] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples in a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description of this article, and are not limited to the specific values ​​​​exemplified below.

[0030] Examples 1-5

[0031] The glass raw materials were accurately weighed according to the molar percentages of the components of Examples 1-5 in Table 1.

[0032] The raw materials weighed according to the above glass composition are fully ground and mixed evenly.

[0033] The ground raw materials are poured into a corundum crucible, and placed in a high-temperature electric furnace at 1450°C for 80 minutes to obtain a uniform glass melt. The melting atmosphere is a N2-H2 mixed gas.

[0034] The melt was poured into a mold preheated to 600°C, and the formed glass was quickly placed in a muffle furnace at 600°C for 2.5 hours for annealing, and then cooled to room temperature with the furnace to obtain a primary scintillating glass product.

[0035] The above-mentioned scintillating glass primary product is processed into scintillating glass of 5×5×5mm, 25×25×5mm and 35×35×5mm after cutting, surface grinding and polishing.

[0036] Examples 1-5 use the same preparation process, the only difference is the luminescent center Ce 3+ The specific composition of the components is shown in Table 1:

[0037] Table 1: Glass composition, density, light yield and decay time of Examples 1-5 Example No. Glass composition (mol%) <![CDATA[Density (g / cm 3 )]]> Light output (Ph / Mev) Decay time (ns) Example 1 <![CDATA[30.5SiO2-25B2O3-10Al2O3-34Gd2O3-0.5CeF3]]> 5.05 393 158(10.3%),530 Example 2 <![CDATA[30SiO2-25B2O3-10Al2O3-34Gd2O3-1CeF3]]> 5.08 443 169(12.2%),511 Example 3 <![CDATA[29.5SiO2-25B2O3-10Al2O3-34Gd2O3-1.5CeF3]]> 5.11 345 127(7.2%),490 Example 4 <![CDATA[29SiO2-25B2O3-10Al2O3-34Gd2O3-2CeF3]]> 5.3 360 119(6.5%),487 Example 5 <![CDATA[31SiO2-25B2O3-10Al2O3-34Gd2O3]]> 5.14 / /

[0038] Embodiment 6-10

[0039] The glass raw materials were accurately weighed according to the mole percentages of the components of Examples 6-10 in Table 2.

[0040] The raw materials weighed according to the above glass composition are fully ground and mixed evenly.

[0041] The ground raw materials are poured into a corundum crucible, and placed in a high-temperature electric furnace at 1300°C and kept warm for 60 minutes to obtain a uniform glass melt. The melting atmosphere is a N2-H2 mixed gas.

[0042] The melt was poured into a mold preheated to 550°C, and the formed glass was quickly placed in a 550°C muffle furnace for 3 hours for annealing, and then cooled to room temperature along with the furnace to obtain a primary scintillating glass product.

[0043] The above-mentioned scintillating glass primary product is processed into scintillating glass of 5×5×5mm, 25×25×5mm and 35×35×5mm after cutting, surface grinding and polishing.

[0044] Examples 6-10 adopt the same preparation process, the only difference is the doping amount of SiO2, B2O3, and GdF3. The specific component compositions are shown in Table 2: Table 2 Glass composition, density, light yield and decay time of Examples 6-10 Example No. Glass composition (mol%) <![CDATA[Density (g / cm 3 )]]> Light output (Ph / Mev) Decay time (ns) Example 6 <![CDATA[30SiO2-25B2O3-5Al2O3-5BaF2-34Gd2O3-1CeF3]]> 5.21 767 125(11.0%),679 Example 7 <![CDATA[25SiO2-20B2O3-5Al2O3-5BaF2-15GdF3-29Gd2O3-1CeF3]]> 5.43 1116 119(7.0%),677 Example 8 <![CDATA[20SiO2-20B2O3-5Al2O3-5BaF2-20GdF3-29Gd2O3-1CeF3]]> 5.62 850 119(6.5%),602 Example 9 <![CDATA[19SiO2-20B2O3-3Al2O3-3BaF2-25GdF3-29Gd2O3-1CeF3]]> 5.79 743 86(7.1%),673 Example 10 <![CDATA[17SiO2-17B2O3-3Al2O3-3BaF2-30GdF3-29Gd2O3-1CeF3]]> 6.03 840 120(9.5%),649

[0045] The density of the scintillating glass prepared by the present invention is obtained by using the Archimedean principle, using pure water as the immersion liquid and weighing it three times with a precision balance and taking the average value; using an absorption spectrometer produced by PerkinElmer, model Lambda950, with a test range of 200 nm-800 nm (ultraviolet visible measurement); using PMT XP2020 to test the decay time; the light yield of all scintillating glasses is 662Kev 137 The measurement was performed in the Cs source gamma-ray transmission mode. The components, density, light yield and decay time of each scintillating glass of Examples 1-10 are shown in Tables 1 and 2; Figure 1 The actual photographs of the scintillating glass obtained in Examples 1-5 of the present invention; Figure 2 is the transmission spectrum of the scintillating glass obtained in Examples 1-5 of the present invention; Figure 3 The decay time measurement spectrum of the scintillation glass obtained in Examples 1-4 of the present invention; Figure 4 are actual photographs of the scintillating glass obtained in Examples 6-10 of the present invention; Figure 5 is the transmission spectrum of the scintillating glass obtained in Examples 6-10 of the present invention; Figure 6 This is a measurement graph of the decay time of the scintillation glass obtained in Examples 6-10 of the present invention.

[0046] Ce prepared by the above method 3+ The gadolinium-doped borosilicate scintillating glass can be further prepared into a scintillating screen. Taking advantage of its viscoelasticity and fluidity at high temperatures, the scintillating glass can be further drawn into an optical fiber, which can be used as a carrier for detecting radiation in a narrow space, and as an optical fiber array for high-resolution medical imaging. It has important application value in the fields of X-ray real-time imaging, industrial online detection, scientific research, and national security monitoring.

[0047] The above description of the embodiments is to facilitate those of ordinary skill in the art to understand and apply the present application. It is obvious that those familiar with the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without having to pay creative labor. Therefore, the present application is not limited to the embodiments herein, and improvements and modifications made by those skilled in the art based on the contents disclosed in the present application without departing from the scope and spirit of the present application are within the scope of the present application.

Claims

1. A Ce 3+ High-density gadolinium-doped borosilicate scintillating glass, characterized in that: The scintillating glass comprises a matrix and luminescent center ions dispersed in the matrix, wherein the proportions of the components in the matrix are: SiO2: 17-31mol%, B2O3: 17-25mol%, Al2O3: 3-10mol%, BaF2: 0-10mol%, GdF3: 0-30mol%, Gd2O3: 15-34mol%, and the luminescent center Ce 3+ The content is 0-2mol%, and the sum of the proportions of the above components is 100%.

2. According to claim 1, Ce 3+ High-density gadolinium-doped borosilicate scintillating glass, characterized in that: The melting atmosphere is a N2-H2 mixed gas.

3. According to claim 1, Ce 3+ High-density gadolinium-doped borosilicate scintillating glass, characterized in that: The melting atmosphere is a N2-H2 mixed gas.

4. A Ce as claimed in any one of claims 1 to 3 3+ The method for preparing doped high-density borosilicate scintillating glass is characterized in that: include: Si source, B source, Al source, Ba source, Gd source and Ce source are used as raw materials, and each molar component of the scintillation glass is uniformly mixed to obtain raw material powder; the obtained raw material powder is melted at 1300-1450°C for 60-80 minutes to obtain a glass melt; the obtained glass melt is poured into a metal mold preheated to 550-600°C, annealed for 2-4 hours after casting and molding, and cooled to room temperature with the furnace to obtain the scintillation glass.

5. The preparation method according to claim 4, characterized in that: The Si source is SiO2.

6. The preparation method according to claim 4, characterized in that: The B source is H3BO3.

7. The preparation method according to claim 4, characterized in that: The Al source is Al(OH)3.

8. The preparation method according to claim 4, characterized in that: The Ba source is BaF2.

9. The preparation method according to claim 4, characterized in that: The Gd source is GdF3, Gd2O3.

10. The preparation method according to any one of claims 4 to 8, characterized in that: The Ce 3+ The source is CeF3.

11. The preparation method according to any one of claims 4 to 9, characterized in that: The purity of the raw material is at least analytically pure.

12. The preparation method according to any one of claims 4 to 10, characterized in that: The annealing treatment temperature is 550-600° C., the annealing time is 2-4 hours, and the scintillation glass is obtained after the temperature is naturally reduced to room temperature during furnace cooling.

Citation Information

Patent Citations

  • A Eu 3+ High-density scintillation glass doped with tellurate and its preparation method

    CN107759079B

  • High-density irradiation-resisting fast flash inorganic glass

    CN1087066A